The Potential of Nanocellulose Acetate as Surfactant for Water-Vegetable Oil Systems - Ibrahim, Ikhsan; Ledyastuti, Mia (Jurnal Kimia Valensi, 2023)
Indonesia, as an agricultural country, has a variety of abundant plants. Cellulose is a component in plants that can be modified to increase its economic value. Resizing cellulose to nanocellulose and modification of nanocellulose to nanocellulose acetate can increase its potential as a surfactant. Resizing cellulose can be done using the strong acid hydrolysis method. An acetic anhydride reagent was utilized to convert the surface hydroxyl functional group into acetyl. The successful production and modification of nanocellulose were confirmed using fourier transform infrared and particle size analysis characterization. The infrared absorption spectrum of cellulose and nanocellulose showed no difference in peaks. Particle size distribution showed that nanocellulose I (CNC I) and nanocellulose II (CNC II) has sizes of 142 nm and 319 nm, respectively. The property of nanocellulose molecules in an oil-water system was simulated using molecular dynamics with GROMACS 2020.6 software. Appropriate trends can be seen in the interfacial tension of water-vegetable oil systems. The value of interfacial tension decreases with the addition of nanocellulose acetate compared to the addition of nanocellulose. With the agreement between the experimental and computational results, nanocellulose acetate can act as a surfactant.